A.R.R.O.W.2: once- vs twice-weekly carfilzomib, lenalidomide, and dexamethasone in relapsed/refractory multiple myeloma - Dimopoulos, Meletios A; Coriu, Daniel; Delimpasi, Sosana; Špička, Ivan; Upchurch, Terry; Fang, Belle; Talpur, Rakhshandra; Faber, Edward; Beksac, Meral; Leleu, Xavier (Blood advances, 2024)
Twice-weekly carfilzomib (27 mg/m2) plus lenalidomide and dexamethasone (KRd27) is a standard of care in relapsed/refractory multiple myeloma (RRMM). Once-weekly carfilzomib regimens have shown clinical benefits with improved patient convenience. This open-label, phase 3, multicenter, randomized study aimed to demonstrate noninferiority of the overall response rate (ORR) for once-weekly carfilzomib (56 mg/m2) plus Rd (KRd56) vs twice-weekly KRd27 in RRMM. A total of 454 patients were randomized (1:1) to receive carfilzomib as once-weekly 30-minute infusions of 56 mg/m2 (KRd56; n = 228) or twice-weekly 10-minute infusions of 27 mg/m2 (KRd27; n = 226). Baseline characteristics were balanced between groups. ORR was 82.5% (95% confidence interval [CI], 76.9-87.2) in the once-weekly group vs 86.3% (95% CI, 81.1-90.5) in the twice-weekly group (risk ratio, 0.954 [95% CI, 0.882-1.032]) and did not meet the threshold for statistical significance of noninferiority (P = .0666). Complete response (CR) or better was obtained in 46.9% of patients in the once-weekly arm and 36.3% in the twice-weekly arm. The proportions of patients who achieved CR and were also assessed negative for minimal residual disease were 21.5% and 18.1%, respectively (odds ratio, 1.235 [95% CI, 0.775-1.970]). Progression-free survival was comparable between groups (hazard ratio, 0.945 [95% CI, 0.617-1.447]). The safety profile was similar for both groups. In conclusion, although statistical significance for noninferiority of ORR was not achieved, the efficacy and safety of once-weekly KRd56 were similar to those of twice-weekly KRd27, and once-weekly KRd56 may be an effective and convenient treatment option for patients with RRMM. This trial was registered at www.ClinicalTrials.gov as #NCT03859427.
Keywords: rozvrh dávkování léků; Oligopeptides; dospělí; Recurrence; Female; Adult; výsledek terapie; ženské pohlaví; lenalidomid; lidé; oligopeptidy; mnohočetný myelom; recidiva; Lenalidomide; Drug Administration Schedule; Treatment Outcome; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Male; Aged; dexamethason; Dexamethasone; lidé středního věku; senioři nad 80 let; Multiple Myeloma; senioři; mužské pohlaví; Middle Aged; Humans